2013
DOI: 10.1002/pc.22687
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of 2‐hydroxyethyl methacrylate–chitosan functionalized multiwall carbon nanotubes nanocomposites

Abstract: Surface of chitosan (CS) functionalized multiwall carbon nanotubes (MWCNTs) was modified by using 2‐hydroxyethyl methacrylate (HEMA) monomers and the composites were synthesized under microwave irradiation. In this approach, multiwalled carbon nanotubes were functionalized with HEMA and CS in two steps. Firstly, CS was grafted onto the surface and side wall of carbon nanotubes by using microwave irradiation. At the second step, HEMA monomers were grafted onto the polymeric matrix surface. The modified surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Fourier‐transform infrared spectra of functionalized single‐walled carbon nanotubes, chitosan and nanocomposite films confirmed the functionalization of the nanofiller and the conservation of chitosan structure after incorporation of single‐walled carbon nanotubes into the polymeric matrix, Figure 3. functionalized single‐walled carbon nanotubes spectra showed low intensity bands at 1719 and 3300 cm −1 , respectively, related to the carboxyl and hydroxyl groups, which evidence the effective functionalization of single‐walled carbon nanotubes, while the band at 1575 cm −1 is related to the aromatic C=C bond stretching [21], Figure 3a. The chitosan spectrum showed the absorption bands characteristics of amides I and II at 1655 and 1560 cm −1 , respectively; −C−H banding at 1409 cm −1 ; C−O and C−O−C stretching vibrations at 1153, 1094 and 1026 cm −1 , corresponding to the saccharide structure of chitosan; and O−H stretching at 3350 cm −1 , Figure 3b.…”
Section: Resultsmentioning
confidence: 99%
“…Fourier‐transform infrared spectra of functionalized single‐walled carbon nanotubes, chitosan and nanocomposite films confirmed the functionalization of the nanofiller and the conservation of chitosan structure after incorporation of single‐walled carbon nanotubes into the polymeric matrix, Figure 3. functionalized single‐walled carbon nanotubes spectra showed low intensity bands at 1719 and 3300 cm −1 , respectively, related to the carboxyl and hydroxyl groups, which evidence the effective functionalization of single‐walled carbon nanotubes, while the band at 1575 cm −1 is related to the aromatic C=C bond stretching [21], Figure 3a. The chitosan spectrum showed the absorption bands characteristics of amides I and II at 1655 and 1560 cm −1 , respectively; −C−H banding at 1409 cm −1 ; C−O and C−O−C stretching vibrations at 1153, 1094 and 1026 cm −1 , corresponding to the saccharide structure of chitosan; and O−H stretching at 3350 cm −1 , Figure 3b.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, -C-H banding at 1409 cm −1 ; C-O and C-O-C stretching vibrations at 1153, 1094 and 1026 cm −1 , corresponding to the saccharide structure of chitosan. A typical band at 1716 cm −1 is attributed to the carboxyl groups, which evidence the effective functionalization of the carbon nanotubes, while the additional observed band at 1579 cm −1 is related to the aromatic C=C bond stretching of its structure, as indicated by the arrows ( Figure 1 b) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rich of hydrophobic and hydrophilic groups, CS can be adsorbed onto MWNTs surfaces via hydrophobic interactions, hydrogen bonding, and so on. The absorbed CS chains make MWNTs hydrophilic and easy to be dispersed . Aroon et al found that CS‐wrapped MWNTs were well dispersed in polyimide matrix and effectively improved the CO 2 /CH 4 separation performance of the composite films.…”
Section: Introductionmentioning
confidence: 99%